Expansion of Autoreactive Unresponsive CD21−/low B Cells in Sjögren's Syndrome–Associated Lymphoproliferation. Issue 4 (28th March 2013) - Saadoun, D.; Terrier, B.; Bannock, J.; Vazquez, T.; Massad, C.; Kang, I.; Joly, F.; Rosenzwajg, M.; Sene, D.; Benech, P.; Musset, L.; Klatzmann, D.; et al.
Abstract: Objective: Primary Sjögren's syndrome (SS) is an autoimmune disease associated with a high risk of developing non‐Hodgkin's lymphoma. This study was undertaken to determine the nature of B cells driving lymphoproliferation in primary SS. Methods: B cell subsets and function were analyzed in peripheral blood from 66 adult patients with primary SS (including 14 patients with B cell lymphoproliferative disease [LPD]) and 30 healthy donors, using flow cytometry, calcium mobilization, and gene array analysis. The reactivity of recombinant antibodies isolated from single B cells from patients with primary SS and LPD was tested using an enzyme‐linked immunosorbent assay. Results: We observed an expansion of an unusual CD21 −/low B cell population that correlated with lymphoproliferation in patients with primary SS. A majority of CD21 −/low B cells from patients with primary SS expressed autoreactive antibodies, which recognized nuclear and cytoplasmic structures. These B cells belonged to the memory compartment, since their Ig genes were mutated. They were unable to induce calcium flux, become activated, or proliferate in response to B cell receptor and/or CD40 triggering, suggesting that these autoreactive B cells may be anergic. However, CD21 −/low B cells from patients with primary SS remained responsive to Toll‐like receptor (TLR) stimulation. Molecules specifically expressed in CD21 −/low B cells that are likely to induce their unresponsive stage were detected in gene array analyses. Conclusion: Patients with primary SS who display high frequencies of autoreactive and unresponsive CD21 −/low B cells are susceptible to developing lymphoproliferation. These cells remain in peripheral blood controlled by functional anergy instead of being eliminated, and chronic antigenic stimulation through TLR stimulation may create a favorable environment for breaking tolerance and activating these cells.